2014
DOI: 10.1111/j.2047-2927.2013.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived stem cell therapy for prevention and treatment of erectile dysfunction in a rat model of Peyronie's disease

Abstract: SUMMARYPeyronie's disease (PD) is a localized connective tissue disorder that involves the tunica albuginea (TA) of the penis. While surgical correction remains the gold standard, the search for an effective and less invasive therapy continues. The objective of this study was to evaluate the effects of intratunical injection of adipose tissue-derived stem cells (ADSCs) for the prevention and treatment of erectile dysfunction in a rat model of PD. Twenty-four male Sprague-Dawley rats (300-350 g) were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 29 publications
(33 reference statements)
4
56
1
1
Order By: Relevance
“…Alternative nonsurgical treatments are continuously being investigated. Recently, intralesional decorin (proteoglycan) 156 and human adipose-derived stem-cell therapy 157,158 have shown promising results in animal models. Further research is needed to determine whether these agents will prove to be safe and effective in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative nonsurgical treatments are continuously being investigated. Recently, intralesional decorin (proteoglycan) 156 and human adipose-derived stem-cell therapy 157,158 have shown promising results in animal models. Further research is needed to determine whether these agents will prove to be safe and effective in humans.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Local injection of ADSCs into the tunica albuginea decreased Peyronie's-like changes by decreasing the expression of tissue inhibitors of metalloproteinases (TIMPs) and increasing expression of matrix metalloproteinases (MMPs), which resulted in decreased elastosis and fibrosis. 21,22 Urethral stricture disease and Peyronie's disease have similar fibrotic properties despite involving different anatomic locations. Both conditions are characterized by the formation of fibrous tissue with the same types of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Another study used an identical rat model to examine the use of ADSCs as a preventative option against corporal fibrosis. 32 The study showed that injecting ADSCs at the time of injury (prevention) showed similar improvement in erectile function when compared to conventional methods of stem cell therapy. Increased levels of the antifibrotic enzymes matrix metalloproteinase and decreased levels of the profibrotic enzymes tissue inhibitors of metalloproteinases added insight into the mechanism of action stem cells utilized to reduce corporal fibrosis.…”
Section: Adiposeederived Stem Cellsmentioning
confidence: 92%